Problems of accounting for the costs of innovation production and ways to solve them - Chernyshenko, O. I. (WSEH, 2024)
The report considers the essence of accounting for costs for innovative production. It is a complex process related to the definition, classification and allocation of costs. Accounting problems arise in connection with the peculiarities of innovation activity, such as high uncertainty, long-term nature and the need to integrate different types of costs. The main problems inherent in innovative production are considered.
Проблеми обліку витрат на інноваційне виробництво та шляхи їх вирішення
Keywords: costs; cost; accounting; innovative production; problems; efficiency